A New Consideration of Scar Formation in Open Rhinoplasty - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2009)
Rhinoplasty is one of the most variable operations in facial plastic surgery because of the various deformities involved and dissimilar methods used to correct them. Although the exposure of the surgical anatomy with an open approach to rhinoplasty is much better than with the endonasal approach, many surgeons focus mainly on the risk of a visible columellar scar. However, despite this unfavorable complication of a midcolumellar incision, a better understanding of the nasal deformities can be gained, and a more detailed reconstruction can be performed. Surgeons have developed various methods to reduce the risk of scar formation. Different incision types include the Z, V, reverse V, and W incisions. In our experience, meticulous inverted V midcolumellar incision closure results in a better scar. There is no convincing reason to reject the transcolumellar incision for external rhinoplasty.
Keywords: Closure technique; columellar scar; rhinoplasty; EXTERNAL RHINOPLASTY; NOSE